Fluvial hydraulics - Dingman, S. L. (Oxford University Press, 2009)
1. Introduction to Fluvial Hydraulics. 2. Natural Streams: Morphology, Materials, and Flows. 3. Structure and Properties of Water. 4. Basic Concepts and Equations. 5. Velocity Distribution. 6. Uniform Flow and Flow Resistance. 7. Forces and Flow Classification. 8. Energy and Momentum Principles. 9. Gradually-Varied Flow and Water-surface Profiles. 10. Rapidly Varied Steady Flow. 11. Unsteady Flow. 12. Sediment Entrainment and Transport. Appendix A: Dimensions, Units, and Numerical Precision.
Keywords: Streamflow.; Fluid mechanics.; elektronické knihy; electronic books